2003
DOI: 10.1590/s0100-204x2003001000004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização genética da raça bovina Crioulo Lageano por marcadores moleculares RAPD

Abstract: Resumo -O objetivo deste trabalho foi a caracterização genética da raça bovina Crioulo Lageano por marcadores RAPD em comparação com as raças Holandesa e Nelore. Foram selecionados 43 primers, que geraram 77 bandas polimórficas. Os animais foram distribuídos em cinco subgrupos de Crioulo Lageano (I a V), e um subgrupo em cada uma das raças Holandesa (VI) e Nelore (VII). A maior parte da variância genética total (65,05%) foi causada pela diferença de indivíduos dentro dos grupos, e o restante pelas diferenças e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 7 publications
3
16
0
5
Order By: Relevance
“…In Nellore bulls the DPP was 18.1 ± 1.9 months of age and also did not influence the onset of other reproductive events in these bulls (Freneau et al, 2006). Based on facts above discussed and that the Crioulo Lageano breed was only submitted to the pressure of natural selection for over three centuries (Spritze et al, 2003), it is suggested that the interval of six months between the onset of puberty in the most and least precocious bull, observed in this experiment, indicates the possibility of selecting those bulls which are potentially more precocious and fertile.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In Nellore bulls the DPP was 18.1 ± 1.9 months of age and also did not influence the onset of other reproductive events in these bulls (Freneau et al, 2006). Based on facts above discussed and that the Crioulo Lageano breed was only submitted to the pressure of natural selection for over three centuries (Spritze et al, 2003), it is suggested that the interval of six months between the onset of puberty in the most and least precocious bull, observed in this experiment, indicates the possibility of selecting those bulls which are potentially more precocious and fertile.…”
Section: Discussionmentioning
confidence: 79%
“…Since this period, the potential of maximum heterosis in the F1 generation has become well known and the results were attributed only to the imported breeds. Due the widespread increase in cross-breeding between these breeds, the population of the Crioulo Lageano breed has been decreasing drastically and a strong tendency persists toward replacement of local breeds with exotic breeds, mainly in southern Brazil (Spritze et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the intragroup average distance is always lower than intergroup average distance. Higher variability between individuals within populations than among populations was also found by Spritze et al (2003) and by Serrano et al (2004) in Brazilian cattle; by Paiva et al (2005) The intragroup distance D (Table 5) ranged from 0.43 (group II) to 1.02 (group III). The presence of Nambi ecotype in group III explains its greater intragroup heterogeneity.…”
Section: Resultsmentioning
confidence: 85%
“…AMOVA (analysis of molecular variance) was to analyze the genetic structure, using the Arlequim v. 2 program that uses an AMOVA adaptation for dominants data, such as RAPD (Stewart Jr & Excoffier, 1996;Schneider at al., 2000). The TFPGA v. 1.3 -Tools for population genetic analysis (Miller, 1997) was used for further among and within population analyses.…”
Section: Methodsmentioning
confidence: 99%